A clinico-ethical framework for multidisciplinary review of medication in nursing homes. Issue 1 (10th December 2014) - Baqir, Wasim; Barrett, Steven; Desai, Nisha; Copeland, Richard; Hughes, Julian
Abstract: Residents in care homes are more likely to be prescribed multiple medicines yet often have little involvement in these prescribing decisions. Reviewing and stopping inappropriate medicines is not currently adopted across the health economy. This Health Foundation funded Shine project developed a pragmatic approach to optimising medicines in care homes while involving all residents in decision making. The pharmacist undertook a detailed medication review using primary care records. The results were discussed at a multidisciplinary team (MDT) meeting involving the care home nurse and the resident's general practitioner (GP), with input from the local psychiatry of old age service (POAS) where appropriate. Suggestions for medicines which should be stopped, changed or started, and other interventions (eg monitoring) were discussed with the resident and/or their family. Over 12 months 422 residents were reviewed, and 1346 interventions were made in 91% of residents reviewed with 15 different types of interventions. The most common intervention (52.3%) was to stop medicines; 704 medicines stopped in 298 residents (70.6%). On average, 1.7 medicines were stopped for every resident reviewed (range zero to nine medicines; SD=1.7), with a 17.4% reduction in medicines prescribed (3602 medicines prescribed before and 2975 after review). The main reasons for stopping medicines were: no current indication (401 medicines; 57%), resident not wanting medicine after risks and benefits were explained (120 medicines; 17%), and safety concerns (42 medicines; 6%). The net annualised savings against the medicines budget were £77, 703 or £184 per person reviewed. The cost of delivering the intervention was £32, 670 (pharmacist, GP, POAS consultant, and care home nurse time) for 422 residents; for every £1 invested, £2.38 could be released from the medicines budget. This project demonstrated that a multidisciplinary medication review with a pharmacist, doctor, and care home nurse can safely reduce inappropriate medication in elderly care home residents.